2018
DOI: 10.1016/j.chemosphere.2018.07.052
|View full text |Cite
|
Sign up to set email alerts
|

What is driving the NF-κB response in environmental water extracts?

Abstract: In vitro bioassays are increasingly applied for water quality monitoring, with assays indicative of adaptive stress responses commonly included in test batteries. The NF-κB assay is responsive to surface water and wastewater extracts, but the causative compounds are unknown and micropollutants typically found in water do not activate the NF-κB assay. The current study aimed to investigate if co-extracted organic matter and/or endotoxins could cause the NF-κB response in surface water extracts. The effect of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Although effects are often observed at low enrichment factors in NF-κB GeneBLAzer, the assay may not be suitable to evaluate the effects of micropollutants. Endotoxins activate NF-κB and a recent study showed that co-extracted endotoxins likely explained most of the effects in surface water extracts in the NF-κB GeneBLAzer assay (Neale et al, 2018b).…”
Section: Nf-κb Responsementioning
confidence: 99%
“…Although effects are often observed at low enrichment factors in NF-κB GeneBLAzer, the assay may not be suitable to evaluate the effects of micropollutants. Endotoxins activate NF-κB and a recent study showed that co-extracted endotoxins likely explained most of the effects in surface water extracts in the NF-κB GeneBLAzer assay (Neale et al, 2018b).…”
Section: Nf-κb Responsementioning
confidence: 99%
“…In that study, Neale et al . 37 also report that the majority of the observed NFĸB effect in four Australian environmental water samples was caused by endotoxins and not environmental pollutants.…”
Section: Resultsmentioning
confidence: 88%
“…NFĸB activity in water samples can be caused by either environmental pollutants or by the presence of endotoxins in the water. It has recently been demonstrated that bacterial lipopolysaccharides (LPS), and potentially other endotoxins, can be co-extracted from the water to the extract when using solid phase extraction methods 37 . In that study, Neale et al .…”
Section: Resultsmentioning
confidence: 99%
“…Inflammatory bowel disease, glomerulonephritis and septic shock have been identified as inflammatory diseases closely associated with NF-κB (31). Studies have shown that NF-κB can be activated by endotoxin to enter the nucleus and regulate the gene expression of various inflammatory mediators, particularly the increase of TNF-α and IL-1β, which further acts on macrophages and other inflammatory mediators and cytokines (32,33). These cytokines further activate NF-κB, thus forming a positive feedback cascade amplification effect, producing an excessive inflammatory response and causing extensive tissue and cell injury (33).…”
Section: Discussionmentioning
confidence: 99%